AN ULTRAVIOLET LASER MICROPROBE FOR THE IN SITU ANALYSIS OF MULTISULFUR ISOTOPES AND ITS USE IN MEASURING ARCHEAN SULFUR ISOTOPE MASS-INDEPENDENT ANOMALIES - Hu G.; Rumble D.; Wang P.L. (My University, 2003)
A laser fluorination microprobe system has been constructed for high-accuracy, high-precision multisulfur isotope analysis with improved spatial resolution. The system uses two lasers: (a) a KrF excimer laser for in situ spot analysis by ultraviolet (UV) photoablation with λ = 248 nm and (b) a CO2 laser for whole-grain analysis of powdered samples by infrared heating at λ = 10.6 μm. A CO2 laser is necessary for the analysis of interlaboratory isotope reference materials because they are supplied as powders. The δ34S and δ33S compositions of reference materials measured with a CO2 laser fluorination system agree (±0.2‰, 1σ) with the recommended values by the Sulfur Isotope Working Group of the International Atomic Energy Agency Ding et al 2001 and Taylor. The precision of replicate analyses of powdered sulfide minerals with the CO2 laser is typically ±0.2‰ (1σ) for δ34S.